Transformasi Hukum Keluarga Islam di Arab Saudi: Analisis Reformasi Regulasi dalam Perspektif Politik Hukum dan Maqāṣid al-Syarī‘ah - Wahyu Febri Yansah; Siah Khisyi’ah (JURNAL ILMIAH NUSANTARA, 2026)
The reform of family law in Saudi Arabia represents a significant step toward modernizing the national legal system by enhancing legal certainty, family protection, and judicial effectiveness. The enactment of the Personal Status Law in 2022 marked a milestone in the codification of Islamic family law, replacing the previous reliance on judicial interpretations of the Hanbali school. This study aims to analyze the transformation of Islamic family law in Saudi Arabia, identify the driving factors behind legal reform, and examine its implications for the development of contemporary Islamic family law. This research employs normative legal research using statutory, conceptual, historical, and comparative approaches. Legal materials were collected through library research, including legislation, Islamic legal literature, scholarly journals, and official government documents. The data were analyzed descriptively and analytically through the perspectives of legal politics and Maqāṣid al-Sharīʿah. The findings indicate that the reform does not alter the fundamental principles of Islamic law but codifies and standardizes legal norms to strengthen legal certainty, improve the protection of women and children, and enhance the efficiency of family dispute resolution. The reform reflects a process of harmonizing Islamic legal principles with the demands of a modern legal system. This study proposes a codification-based model of Islamic family law transformation as a conceptual contribution to the development of family law in Muslim-majority countries.